Risk Factors for Mortality in Patients with Serratia marcescens Bacteremia - Kim, Sun Bean; Jeon, Yong Duk; Kim, Jung Ho; Kim, Jae Kyoung; Ann, Hea Won; Choi, Heun; Kim, Min Hyung; Song, Je Eun; Ahn, Jin Young; Jeong, Su Jin; Ku, Nam Su; Han, Sang Hoon; et al. (Yonsei medical journal, 2015)
Over the last 30 years, Serratia marcescens (S. marcescens) has emerged as an important pathogen, and a common cause of nosocomial infections. The aim of this study was to identify risk factors associated with mortality in patients with S. marcescens bacteremia. We performed a retrospective cohort study of 98 patients who had one or more blood cultures positive for S. marcescens between January 2006 and December 2012 in a tertiary care hospital in Seoul, South Korea. Multiple risk factors were compared with association with 28-day all-cause mortality. The 28-day mortality was 22.4% (22/98 episodes). In a univariate analysis, the onset of bacteremia during the intensive care unit stay (p=0.020), serum albumin level (p=0.011), serum C-reactive protein level (p=0.041), presence of indwelling urinary catheter (p=0.023), and Sequential Oran Failure Assessment (SOFA) score at the onset of bacteremia (p<0.001) were significantly different between patients in the fatal and non-fatal groups. In a multivariate analysis, lower serum albumin level and an elevated SOFA score were independently associated with 28-day mortality [adjusted odds ratio (OR) 0.206, 95% confidential interval (CI) 0.044-0.960, p=0.040, and adjusted OR 1.474, 95% CI 1.200-1.810, p<0.001, respectively]. Lower serum albumin level and an elevated SOFA score were significantly associated with adverse outcomes in patients with S. marcescens bacteremia.